A visão da cidade em Marques Abreu - Borges, P. A. (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
The work of Marques Abreu has always been perceived as promotion, defense and editing in the field of build heritage, emphasising the North Romanesque. In spite of not being born in Porto, the author adopted this city by scrolling and portraying it with the knowledge of the cross readings of Craig Annan, Jacob Riis, Frederick Evans and Benjamin Stone, fleeing the sterotype outlined by biel or Aurélio Paz dos Reis, but closer to delayed phase of Cunha Moraes. In his many works which portray the urban reality, Porto stands out, but there's also insights of Caminha, Viana do Castelo, Vila do Conde, Sintra, Évora and Lisbon, with incursions into smaller urban areas. He has always sought to understand the urban reality, dismouting plots that would allow him to rebuild the wole of the urban core, not limiting to build heritage, pouring out instead to other works fields where he would be less at ease. [...]